PENGARUH PENAMBAHAN URASIL DALAM MEDIA FERMENTASI TERHADAP HASIL β-GLUKAN DARI DUA GALUR AGROBACTERIUM - Kusmiati, Kusmiati; Tamat, Swasono R.; Nuswantara, Sukma; Muhamad, Salmah (Makara Journal of Science, 2007)
Influence of Uracil in Fermentation Media on β-Glucan Production by Agrobacterium Radiobacter A 1.5 and Agrobacterium sp. Bro 1.2.1. Optimum β-glucan production can be achieved by an optimum condition in the fermentation media. Uracil, as a precursor of UDP-glucose, may act as a glucose donor in the formation of polysaccharides such as β-glucan. It is expected that addition of certain quantity of uracil into the fermentation media in a suitable growth phase of Agrobacterium radiobacter A 1.5 and Agrobacterium sp. Bro 1.2.1, will significantly increase the β-glucan production. In this investigation, 0.025%; 0.05% or 0.1% of uracil were added into the fermentation media during the logarithmic phase (24 hour) or stationary phase (46 hour) of growth. The β-glucan product was evaluated from the β-glucan (crude) dry-weight and from the β-glucan content. Beta-glucan content was determined as glucose by the Hisamatsu-AOAC and HPLC methods. The highest β-glucan (crude) dry-weight produced by the A. 1.5 was in a medium containg 0.025% uracil (24 hour), whilst by the A. Bro 1.2.1 was in a medium containg 0.1% uracil (46 hour), both higher than control. The highest β-glucan content produced by the A. 1.5 (27.03%) was in a medium containg 0.025% uracil (46 hour), while control produced only 23.28%. The highest β-glucan content produced by the Bro 1.2.1 (29.34%) was in a medium containg 0.025% uracil (24 hour), while control produced only 28.75%. Two-way anova analysis showed that there were no significant influence difference (α = 0,05) from various concentration of uracil in either growth phases, to the yield of β-glucan (crude) dry-weight nor to the β-glucan equivalent glucose content.